2017
DOI: 10.1007/s10103-017-2226-6
|View full text |Cite|
|
Sign up to set email alerts
|

Nd:YAG laser irradiation associated with fluoridated gels containing photo absorbers in the prevention of enamel erosion

Abstract: This study evaluated the combined effect of Nd:YAG laser irradiation and fluoridated gels containing photo absorbers against enamel erosion. Enamel specimens from bovine teeth were polished, eroded (10 min, with 1% citric acid, pH = 2.6), and randomly allocated into the experimental groups (n = 8), according to the different surface treatments: fluoridated gels (F: 9047 ppm F and F + Sn: 9047 ppm F and 3000 ppm Sn), with or without photo absorbers (E: erythrosine and MB: methylene blue), and associated or not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…Many studies have assessed the efficacy of fluoride alone and in combination with other protective measures in the prevention of erosion. 3,24,[39][40][41][42] Laser irradiation alone or combined with fluoride application has also been suggested to increase enamel acid resistance, 31,43 and some studies demonstrated the positive efficacy of Er:YAG laser in increasing enamel resistance against acid attacks and dental caries. 30,31,44 Although both caries and erosion are caused by the demineralization of enamel, their main etiologic factors and mechanism of development are totally different.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have assessed the efficacy of fluoride alone and in combination with other protective measures in the prevention of erosion. 3,24,[39][40][41][42] Laser irradiation alone or combined with fluoride application has also been suggested to increase enamel acid resistance, 31,43 and some studies demonstrated the positive efficacy of Er:YAG laser in increasing enamel resistance against acid attacks and dental caries. 30,31,44 Although both caries and erosion are caused by the demineralization of enamel, their main etiologic factors and mechanism of development are totally different.…”
Section: Discussionmentioning
confidence: 99%
“…The dental erosion cycling was carried out according to a previously described protocol [24]. The specimens were immersed in 4 ml of 0.3% citric acid solution (natural pH of 2.6) for 5 min, without agitation, followed by 60-min exposure to artificial saliva under gentle agitation at 150 rpm [25].…”
Section: Erosive and Erosive-abrasive Cyclingmentioning
confidence: 99%
“…(pH natural de aproximadamente 2,6), por 10 min. Em seguida as fitas de UPVC foram removidas e os espécimes foram analisados em perfilômetro ótico para certificar que todos os espécimes possuíam lesões padronizadas, entre 2-5 m, para os dois substratos (70,71,116).…”
Section: Lesão Inicialunclassified